(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
The quality of pharmaceuticals has been a concern of the World Health Organization (WHO) since its inception. This includes the quality of starting materials, including active substances and excipients, for the production of medicinal products and here packaging materials are also covered. Any risks that may emanate from starting materials of inappropriate quality must be avoided for the benefit and safety of patients using medicinal products. Drug products are complex mixtures of drug and excipients, and as such, their chemical and physical stability kinetics are complex. A thorough knowledge of the chemical and physical stability of drugs and dosage forms is critical in the development and evaluation of pharmaceuticals. Each ingredient, whether therapeutically active or pharmaceutically necessary, can affect the stability of drug substances and dosage forms.It is most important to ensure that a particular formulation when packaged in a specific container will remain within its physical, chemical, microbiological, therapeutic and toxicological specifications on storage for a specified time period. In order to have such an assurance we need to conduct a rigorous stability testing program on the product in the form that is finally to be marketed. This paper presents a reasonably systematic and comprehensive approach to the subject of chemical and physical drug stability and the factors affecting drug stability.